Oud neg.nr. 7457-7463. 'Bouwwerkgevers, Sociaal Fonds Bouwnijverheid, Nelissen, Langeraar, de Kievit' - Haas, Joh. de,
Oud neg.nr. 7457-7463. 'Bouwwerkgevers, Sociaal Fonds Bouwnijverheid, Nelissen, Langeraar, de Kievit'.